CONTINUITY OF GEOMETRY TEACHING AT SCHOOL AND UNIVERSITY - Мynzhasarova, М.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
At school, each student must be given a geometric education in accordance with the updated content of education. This is due to the fact that geometry is taught in the first academic year of higher education as a separate subject in the field of physics and mathematics, and in technical - as one of the main subjects in higher mathematics. First-year students face difficulties in mastering this discipline. Because, firstly, the geometric knowledge of the student is not high enough, and secondly, the number of hours allocated to the development of this discipline at the university is small. The article considers the problem of continuity of teaching geometry at school and university. Continuity requires a comprehensive approach in a bilateral, that is, substantive and procedural terms. In determining the continuity of the content, an analysis of geometry curricula at school and university was carried out. As a result of the analysis, perspective-continuity relationships in the requirements of the geometry discipline programs are revealed. From the point of view of procedural continuity, the organization of the process of teaching geometry at school and university was compared. The article presents methodological guidelines aimed at implementing continuity in teaching geometry to first-year students.